Rewards and challenges of providing HIV testing and counselling services: health worker perspectives from Burkina Faso, Kenya and Uganda - Bott, Sarah (Health Policy Plan, 2015)
The rapid scale-up of human immunodeficiency virus (HIV) testing, counselling and treatment throughout sub-Saharan Africa has raised questions about how to protect patients’ rights to consent, confidentiality, counselling and care in resource-constrained settings. The Multi-country African Testing and Counselling for HIV (MATCH) study investigated client and provider experiences with different modes of testing in sub-Saharan Africa. One component of that study was a survey of 275 HIV service providers in Burkina Faso, Kenya and Uganda that gathered quantifiable indicators and qualitative descriptions using a standardized instrument. This article presents provider perspectives on the challenges of obtaining consent, protecting confidentiality, providing counselling and helping clients manage disclosure. It also explores health workers’ fear of infection within the workplace and their reports on discrimination against HIV clients within health facilities. HIV care providers in Burkina Faso, Kenya and Uganda experienced substantial rewards from their work, including satisfaction from saving lives and gaining professional skills. They also faced serious resource constraints, including staff shortages, high workloads, lack of supplies and inadequate infrastructure, and they expressed concerns about accidental exposure. Health workers described heavy emotional demands from observing clients suffer emotional, social and health consequences of being diagnosed with HIV, and also from difficult ethical dilemmas related to clients who do not disclose their HIV status to those around them, including partners. These findings suggest that providers of HIV testing and counselling need more resources and support, including better protections against HIV exposure in the workplace. The findings also suggest that health facilities could improve care by increasing attention to consent, privacy and confidentiality and that health policy makers and ethicists need to address some unresolved ethical dilemmas related to confidentiality and non-disclosure, and translate those discussions into better guidance for health workers.